2008
DOI: 10.1016/j.cytogfr.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs and death receptors

Abstract: Death receptors induce apoptosis through either the Type I or Type II pathway. In Type I cells, the initiator caspase-8 directly activates effector caspases such as caspase-3, whereas in Type II cells, the death signal is amplified through mitochondria thereby activating effector caspases causing cell death. Recently, there have been advances in elucidating the early events in the CD95 signaling pathways and how posttranslational modifications regulate CD95 signaling. This review will focus on recent insights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 114 publications
0
36
1
Order By: Relevance
“…MicroRNAs are known to play critical roles in development, cell proliferation, and other fundamental cellular processes (Cimmino et al 2005;Rougvie 2005;Gu and Iyer 2006;Johnson et al 2007;Park and Peter 2008). In addition, miRNAs have also been suggested to be involved in the CSR; however, a few fundamental questions remain largely unanswered (Cimmino et al 2005;Leung et al 2006;Marsit et al 2006;Kulshreshtha et al 2007;Leung and Sharp 2007;Babar et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are known to play critical roles in development, cell proliferation, and other fundamental cellular processes (Cimmino et al 2005;Rougvie 2005;Gu and Iyer 2006;Johnson et al 2007;Park and Peter 2008). In addition, miRNAs have also been suggested to be involved in the CSR; however, a few fundamental questions remain largely unanswered (Cimmino et al 2005;Leung et al 2006;Marsit et al 2006;Kulshreshtha et al 2007;Leung and Sharp 2007;Babar et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the involvement of miRNAs in apoptosis signaling (5). For instance, miR-15 and miR-16 have been shown to induce apoptosis by targeting Bcl-2 (6).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…Cell apoptosis is a complex process that may be achieved through the death-receptor or the mitochondria pathways [55,56]. Most antitumor drugs such as antimetabolites, and alkylating agents inhibit cancer proliferation by promoting cell apoptosis or cell cycle arrest.…”
Section: Mirnas Involved In Chemoresistance Through Cell Apoptosis Rementioning
confidence: 99%